Effect of Principal's Transformational Leadership Style on Teacher Performance - Rahayu, Bekti; Idris, Fahmi; Herawati, Tuti (Universitas Malikussaleh, 2019)
The purpose of this study is to examine how Transformational Leadership is Teacher Performance. Research methods; descriptive analysis, quantitative approach, product moment correlation analysis techniques, determination and regression. Data collected through questionnaires. The population in this study were teachers in two elementary schools in East Bogor City, totaling 54 people, with a total sample of 34 respondents with simple random sampling technique. The results showed a significant relationship between transformational leadership and teacher teaching performance. The recommendation to improve teacher performance is to improve the dimensions of intellectual stimulation and the sensitivity of individual principals and teacher participation in training to improve teacher professional competence.